PEMANFAATAN CLAY EX. BENGALON SEBAGAI AGREGAT BUATAN DAN PASIR EX. SAMBOJA DALAM CAMPURAN BETON DENGAN METODE (AMERICAN CONCRETE INSTITUTE) ACI 211 - Darmansyah, Abdurrahim (KURVA S JURNAL MAHASISWA, 2014)
This study used a mixed design (American Concrete Institute) ACI 211.1 That is done in the laboratory by using artificial coarse aggregate size is the size of coarse aggregate uniform artificial 10 and 40 mm. The sample used for each size of coarse aggregate uniforms made in numbered 30 samples.Â The results of the overall test that the clay ex. Bengalon have a fairly high abrasion value is 60,08% in aggregate categories that can not be used as coarse aggregate for concrete structural class II and quality of K-125, K-175 and K-225 with abrasion condition (27-40%), a very high absorption values ranged 20,223% that control water demand in the concrete mix is relatively difficult, and low yields an average compressive strength of 28 days produced by the method ACI 211 for ukaran coarse aggregate 10 mm and 40 mm is 9,851 and 9,991 MPa of compressive strength of concrete were targeted (f'cr) = 25,7 MPa.